Effectivity of Science E-Modules Based on Multiple Representation of Vibration, Wave and Sound to Improve Problem Solving Skills Junior High School Students - Marhestian, Sherin; Mahardika, I Ketut; Ahmad, Nur (Universitas Negeri Padang, 2023)
Learning system that is in line with the 21st century, education has an impact on how society develops in the period of society 5.0. Along with enhancing comprehension, science education also tries to equip pupils with additional problem-solving abilities. The usage of instructional materials, specifically, is one way to help students' problem-solving abilities in science learning. Multiple representation-based e-modules that are interactive teaching aids. Research and development (R&D) is the approach taken in this field of study. The N-Gain test is a data analysis tool used to evaluate the efficacy of the e-module. Data is transformed into percentages, then examined and divided into many categories. the outcomes of getting an effectiveness score of 0.71 with a high category using the n-gain test. Based on the findings of the research, it can be said that the multiple representation-based science e-module designed to help junior high school students with their problem-solving abilities has been successful and is suitable for use in the classroom as a teaching tool.